2017
DOI: 10.1177/2211068217696779
|View full text |Cite
|
Sign up to set email alerts
|

Companion and Point-of-Care Sensor System for Rapid Multiplexed Detection of a Panel of Infectious Disease Markers

Abstract: A nanochannel-based electrochemical biosensor has been demonstrated for rapid and multiplexed detection of a panel of three biomarkers associated with rapid detection of sepsis. The label-free biosensor detected procalcitonin (PCT), lipoteichoic acid (LTA), and lipopolysaccharide (LPS) from human whole blood. The biosensor comprises a nanoporous nylon membrane integrated onto a microelectrode sensor platform for nanoconfinement effects. Charge perturbations due to biomarker binding are recorded as impedance ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Multiplex microfluidics for protein-based biomarkers are often integrated with immunoassay methodology. This approach has been used, for instance, to detect CRP and PCT to diagnose sepsis [ 90 , 91 ]. Another example is a paper-based microfluidics device that uses a unique 3D paper structure to detect multiple biomarkers (the design concept illustrated in Figure 2 C3) [ 92 ].…”
Section: Potential Multiplex Poct Discriminative Devicesmentioning
confidence: 99%
“…Multiplex microfluidics for protein-based biomarkers are often integrated with immunoassay methodology. This approach has been used, for instance, to detect CRP and PCT to diagnose sepsis [ 90 , 91 ]. Another example is a paper-based microfluidics device that uses a unique 3D paper structure to detect multiple biomarkers (the design concept illustrated in Figure 2 C3) [ 92 ].…”
Section: Potential Multiplex Poct Discriminative Devicesmentioning
confidence: 99%
“…This test is commonly used and formalized in the European, United States, and Japanese Pharmacopeias as the bacterial endotoxin test. 12–15 A previous study reported a shift in the maximum absorbance wavelength of 1 nm. 30 Since the resolution limit of the used plate reader is 2 nm, an aberrance in the spectrum was neither detected nor considered.…”
Section: Resultsmentioning
confidence: 98%
“…Endotoxins, which are also called lipopolysaccharides (LPSs) from a chemical point of view, present a major hazard, because they are known to cause sepsis in humans. 3,4 It is estimated that sepsis potentially leads to about 6 million deaths per year worldwide. 5…”
Section: Introductionmentioning
confidence: 99%
“…While there are a number of methods available for the detection of cancer biomarkers, these biomarkers are most often identified as genes, microRNA, or proteins that are uniquely expressed or silenced in metastatic cancer. 512 Such biomarkers include heat shock protein 70 (Hsp70), epithelial cadherin (E-cadherin), and death-associated protein kinase (DAPK). 1315 Many of these biomarkers were identified through increased understanding of the underlying molecular mechanisms of metastasis progression.…”
Section: Introductionmentioning
confidence: 99%